The Relative Efficiency of Educational Systems: A Cross Country Prescriptive Analysis - Dolton, Peter; Marcenaro-Gutiérrez, Óscar David (My University, 2017)
How does a country achieve the most efficient education system possible? We examine the efficiency of educational systems across the world using internationally comparable performance of secondary school pupils. We use OECD aggregate panel data on 39 countries across 17 years to model the most efficient combination of teacher salaries, class size and capital resources to secure the maximum level of students’ achievement. In the face of constrained education budgets prescriptive policy evaluations are provided to suggest how countries could make a significant improvement to their educational outcomes by adjusting their educational resource inputs. We also ask if there is a trade-off between the efficiency and equity of educational provision.
Keywords: Educación; Educational efficiency; Equity; DEA; stochastic frontier analysis